2021
DOI: 10.1016/j.cytogfr.2020.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Type I IFN-dependent antibody response at the basis of sex dimorphism in the outcome of COVID-19

Abstract: Highlights Sex-based outcome of SARS-CoV-2 infection accounts for about 70% of male deaths, despite similar susceptibility to infection. TLR7/IFN-α axis in pDCs is crucial for B-cell activation and it is at the basis of dimorphic antibody response. Dysregulated and unbalanced IFN-driven B cell response affects COVID-19 outcome in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 92 publications
1
18
0
Order By: Relevance
“…This idea is also supported by a recent report showing that loss-of-function mutation of X-chromosomal TLR7 is associated with impaired type I IFN responses of young male patients with severe COVID-19 that further emphasizes the importance of intact TLR7-mediated type I IFN responses in the pathogenesis of the disease [289]. Moreover, pDC-derived type I IFNs mediate B cell activation and differentiation into plasma cells, thus are essential to elicit an optimal antibody response to viral infection including SARS-CoV-2 infection as well [290].…”
Section: Discussionmentioning
confidence: 99%
“…This idea is also supported by a recent report showing that loss-of-function mutation of X-chromosomal TLR7 is associated with impaired type I IFN responses of young male patients with severe COVID-19 that further emphasizes the importance of intact TLR7-mediated type I IFN responses in the pathogenesis of the disease [289]. Moreover, pDC-derived type I IFNs mediate B cell activation and differentiation into plasma cells, thus are essential to elicit an optimal antibody response to viral infection including SARS-CoV-2 infection as well [290].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, IFN-α production following TLR7 stimulation is greater in pDC from females than from males. It has been hypothesized that type I IFN production by pDC may control early SARS-CoV-2 infection in females better than in males, leading to better outcomes on average and explaining why 70% of those who die from the disease are male [ 59 ].…”
Section: DC and Innate Immunity To Covid-19mentioning
confidence: 99%
“…For the most appropriate viral response, DCs instruct T cells toward anti-viral Th1 via the production of instructive innate cytokines, such as IFN-β and IL-12, which leads to the production of IFN-γ and proper viral clearance [ 45 ]. However, many respiratory viral infections, such as RSV, RV, and SARS-CoV-2, have the ability to dampen type-1 immunity through multiple mechanisms [ 46 , 47 , 48 , 49 , 50 , 51 ] that lead to a decrease in T cell production of important anti-viral cytokines, such as IL-2 and IFN-γ. These skewed responses lead to an imbalanced immune response away from Th1 anti-viral immunity toward a predominantly Th2/Th17 pathogenic response accompanied by a diminished CD8+ cytotoxic T cell response.…”
Section: Overview Of Immune Response To Respiratory Virusesmentioning
confidence: 99%
“…Perhaps these trained immune responses to early-life vaccines may contribute to the protection observed in children during SARS-CoV-2 infections that wanes as we age. On the other hand, studies have linked inappropriate DC-specific trained immunity that leads to a decrease in type-1 IFN levels as a possible route for enhanced COVID-19 disease in susceptible populations [ 49 ]. These observations, along with other studies that have shown that DCs from naturally infected individuals have decreased sensitivity to future unrelated TLR signaling [ 65 , 66 ], suggest that proper activation of DCs and appropriate TLR targeting (i.e., to enhance Th1 immunity) during vaccination may lead to “training” of innate responses to future encounters with unrelated pathogens.…”
Section: Overview Of Immune Response To Respiratory Virusesmentioning
confidence: 99%
See 1 more Smart Citation